Organization change : creating new business line merging two corporation’s units into one - Kivistö, Tiia (2009)
This study is concentrated with change management when merging two separate units inside a corporation. Change in organization affects the balance and that creates already movement in organization. Studying these is concentrated to study this particular two unit’s change into one. The target is to find out what is the situation at the new unit after five months has passed since the official announcement of the merge. The additional target was to find areas and aspects that need corrective actions for the management. This study is concentrating on interviewing the personnel and management from the new united unit (later unit Q). This study is based on change management theories such as Kotter’s eight change management steps and Kvist and Kilpiä’s guidance how to ensure the smooth change in the organization (Kotter 1996, Kvist & Kilpiä 2006). The results have been analyzed and presented according to the themes also found in questions. The study creates an image what the situation during the interviews. The results of this study indicate what corrective actions can be made in the organization and what areas have been managed well during change.